The influence of spiritual leadership on work engagement - Triharjanti, Dessy; Tjahjono, Heru Kurnianto (Asian Journal of Islamic Management (AJIM), 2023)
Purpose – This study aimed to analyze the influence of spiritual leadership on work engagement with psychological empowerment as an intervening variable at Muhammadiyah Junior High School in Yogyakarta.Methodology – The subject in this study, a sample of 129 respondents, was selected by the census method. The analysis tool used is path analysis, which is calculated using the Structural Equation Modeling (SEM) analysis technique operated using the AMOS program.Findings – The results indicated that a higher level of spiritual leadership will increase psychological empowerment and work engagement for yogyakarta teachers in Muhammadiyah Junior High School.Implications – In this study, the researcher gave respondents questionnaires through the school's deputy head or curriculum sector. Owing to the tight schedule of the respondents, the researchers did not accompany them in filling out the questionnaire. This allowed the researcher to know whether the respondent filled out the questionnaire correctly, so there was no potential for bias in filling out the questionnaire.Originality – This research model includes independent variables, dependent variables, and mediation. The independent variables describe spiritual leadership, the dependent variable describes work engagement, and the mediation variable describes psychological empowerment